Digination : identity, organization, and public life in the age of small digital devices and big digital domains - MacDougall, Robert C. (Fairleigh Dickinson University Press series in communication studies., 2012)
Digination offers an inter-disciplinary, broad overview of the psychic, social, and institutional effects of some of the most popular digital communication technologies and applications operating today. Written in an engaging style appropriate for non-specialist readers interested in broadening their awareness and enhancing their understanding of popular trends in media use.